2005
DOI: 10.1136/oem.2005.019760
|View full text |Cite
|
Sign up to set email alerts
|

Age at exposure to ionising radiation and cancer mortality among Hanford workers: follow up through 1994

Abstract: Background: Studies of workers at the plutonium production factory in Hanford, WA have led to conflicting conclusions about the role of age at exposure as a modifier of associations between ionising radiation and cancer. Aims: To evaluate the influence of age at exposure on radiation risk estimates in an updated follow up of Hanford workers. Methods: A cohort of 26 389 workers hired between 1944 and 1978 was followed through 1994 to ascertain vital status and causes of death. External radiation dose estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 44 publications
2
13
0
2
Order By: Relevance
“…The excess risk of all solid cancers and lung cancer appeared restricted to exposure ages 35 years or greater. Evidence from other studies has also suggested associations between radiation dose and lung cancer that are stronger at older exposure ages . However, methods have varied among studies and differences in age‐risk patterns between studies are apparent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excess risk of all solid cancers and lung cancer appeared restricted to exposure ages 35 years or greater. Evidence from other studies has also suggested associations between radiation dose and lung cancer that are stronger at older exposure ages . However, methods have varied among studies and differences in age‐risk patterns between studies are apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from other studies has also suggested associations between radiation dose and lung cancer that are stronger at older exposure ages. 7,[22][23][24] However, methods have varied among studies and differences in age-risk patterns between studies are apparent. These inconsistencies may result from underpowered analyses given low baseline cancer risk at young attained ages.…”
Section: Solid Cancersmentioning
confidence: 99%
“…In a case-control study in four DOE sites, Wing et al [2000] observed an association between the risk of multiple myeloma and low-level whole body penetrating ionizing radiation dose at older ages. A specific association between cancer mortality and radiation doses accrued at older ages has been reported in studies of Hanford workers [Kneale et al, 1984;Kneale and Stewart, 1993], and this association appears particularly strong for lung cancer [Wing and Richardson, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…Such a prospect then becomes one of the more insidious aspects of the Panopticon. Not only will surveillance mold our activities into a constrained pattern, but our past geographies will truly come back to haunt us, much as they have for those who worked in the Hanford nuclear facilities (e.g., Gilbert, Cragle, and Wiggs 1995;Wing and Richardson 2005), but in far more subtle ways.…”
Section: Health For Examplementioning
confidence: 99%